The Effectiveness of Self-Regulation Strategies to Increase Achievement Motivation in Elementary School Students - Wibowo, Bagas Fevernova; Minsih, Minsih (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Good academic achievement will be fulfilled if students have the motivation to excel but some students have problems with the motivation to achieve. The purpose of this study is to test the effectiveness of self-regulation strategies in increasing student achievement motivation. Methodology: This study uses an experimental quantitative method with a one group pre-test post-test research design. The sampling technique used purposive sampling, a research sample of 10 students in grade V of SDN Kedung Waduk 01 Sragen. The data collected is in the form of a score in the form of a percentage. The validity of the data was tested using pretest and posttest. Data analysis was carried out using the Wilcoxon Signed-Rank Test. Main Findings: The results of the study showed an increase in the percentage of student achievement motivation indicators by 71.2 (high) from the initial condition of 25.9 (low). Self-regulation strategy with a standard deviation of 09.95 and a standard error mean of 4.70. After receiving treatment, the self-regulation strategy was seen to increase with a standard deviation of 8.74 and a mean error standard of 4.00. Novelty/Originality of this study: It can be concluded that the motivation of students to achieve achievement after receiving treatment (Self Regulation Strategy) is higher before receiving treatment (Self Regulation Strategy).